RULES VERSUS DISCRETION: THE PRODUCTIVITY CONSEQUENCES OF FLEXIBLE REGULATION. - Majumdar, S. K.; Marcus, A. A. (Academy of Management Journal, 2001)
Using data from electric utilities, this study shows that spending on well-designed regulations has a positive productivity impact but that spending on less well-designed regulations has a negative effect. Better-designed regulations are flexible and grant firms latitude on how to meet goals, allow them time to deploy new means to meet goals, and set ambitious goals that stretch them beyond current practices.